Cardiac clearance of NCAA athletes following SARS-CoV-2 infection in an electrophysiology/cardiology clinic at an osteopathic medical center - Jaramillo Jr., N.; Heller, M.; Zwibel, H.; Cohen, T. J. (EPLab Digest, 2021)
With over 4.6 million deaths and 225 million reported cases, the COVID-19 (SARS-CoV-2) pandemic continues to negatively affect the lives of many worldwide.1 Athletes have been significantly affected, from cancellation of athletic events to unexpected cardiopulmonary complications despite optimal health. Cardiovascular function is paramount for athletes, and studies have demonstrated that severe cardiac complications can occur following SARS-CoV-2 infection, including myocarditis,2,3 myocardial injury (elevated troponin),4 heart failure, and arrhythmias.5 Due to a paucity of clinical data, the prevalence of cardiac pathology in athletes following SARS-CoV-2 infection is unknown.